Wawasan Al-Qur’an Tentang Manusia (Antropologi-Profetik) - Mohammad Subhi (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2016)
Anthropological concept of the Qur’an can be tracked based on the key concepts which describe the human face as a whole. Basyarand insandescribe human beings as biological creatures, human beings as a creature who has the integrity of the soul, and body. Then, clay (tin, hamaim Masnun, Turab) and ruhreveal about human-forming elements, namely land and the spirit of the Divine. Then fitrahand hubuthdescribe the state of the primal, primordial human beings a acreature who has a tendency divinity and the men who Their own degrees of humanity had fallen down for their own behavior. Lastly, ‘abdand khalifahelaborated on the role of humans as the slaves of Allah who passively accept His will, at the same time, actively, realizing His will on the earth.